Pengembangan Soal Literasi Matematis untuk Mendukung Matematisasi Mahasiswa Calon Guru - Lestariningsih, Lestariningsih; Lutfianto, Moch. (Jurnal Elemen, 2021)
Mathematisation ability of prospective teachers that was low in solving mathematical literacy problems needs serious attention. Therefore, to help prospective teachers do mathematization, they were employed by giving mathematical literacy problems. This study aims to produce mathematical literacy problems that were valid, practical, and have potential effects on the mathematization ability of prospective teacher students. The study was conducted using a design research type development study. Thirty students of prospective teachers in a private university in Sidoarjo became the subjects. Mathematical literacy problems’ qualities from this research should support prospective mathematics teachers in categorizing horizontal and verticalization activities. In addition, the problems were designed using the Program for International Student Assessment (PISA) framework with the Indonesian context. The results suggested that the developed mathematical literacy problems could be categorized valid based on validators’ evaluation, practically based on the small group phase results, and have the potential effects were assessed from the results of student tests handed in field test phase using mathematical literacy problems. The test results showed that 78% of prospective mathematics teachers were in the good category of mathematization ability after using the developed problems. The developed mathematical literacy problem has a potential effect so that it can be used as an alternative question in lecturing higher education activities to support the mathematics of prospective teacher students.